Cytotoxic mechanism study of damnacanthal and nordamnacanthal of morinda citrifolia roots in vitro - Wan Norsalehah Wan Abdullah
Natural products have been considered as valuable sources for anticancer drug discovery. Damncanthal (DAM) and nordamnacanthal (NDAM), are two anthraquinones derived from roots of Morinda cilrifolia (family Rubiaceae). The purpose of this study is to evaluate the cytotoxic mechanism of DAM and NDAM in vitro. The cytotoxic effects of DAM and NDAM, were investigated against several cancerous cell lines such as CEM-SS), WEI-II-3B, HT29, MCF-7, DBTRG, Hel,a, and HL-60 cells. The percentage of cell viability was determined using a microtetrazolium assay (MTT). I-I L-60 was observed to be the most sensitive cell line towards DAM and NDAM with CDso values of 10 ug/ml and 11.5 ug/ml for DAM and NDAM, respectively. Meanwhile the CDso value for WEHI-3B cells treated with DAM and NDAM was 24 ug/rnl and 27 ug/ml, respectively. On the other hand, the viability of normal peripheral blood mononuclear cells (PBMC) was not affected. Both compounds also exhibited time-dependent inhibitory effects of the cell line growth, evidenced by the reduction in cell viability and number of viable cells as determined from the trypan blue exclusion assay. From the flow cytometric analysis on the cell cycle of both cell types, it could be observed that both compounds induced apoptosis in WEHI-3B and HL-60 cells, respectively. The percentage of sub-G 1 population of I-IL-60 cells increased from 2.5% to 19. I % after treatment with DAM and from 2.5% to 18.6% after treatment with NDAM. These compounds also induced cell cycle arrest in S-phase for HL-60 and WEHI-3B cells. The microscope analysis on the treated HL-60 and WEHI- 3B, including light microscopy, showed that these compounds induced two types of cell death: apoptosis and necrosis. Fluorescence microscopy following staining with low concentration of acridine orange and propidium iodide (AO/PI) were used to visualize morphological changes of viable, apoptotic, or necrotic cells simultaneously. The early apoptotic stages of WEI-II-3B and HL-60 cells treated with CDso DAM and NDAM were assessed by measuring the quantity of Annexin-positive cells. Cells in their late apoptosis were assessed by measuring the quantity of cells stained with propidium iodide. DNA damage detection using a comet assay was also performed. The result showed that there was a concentration-dependent increase in D A damage in the cells studied prior to cytotoxicity. Both compounds showed early apoptosis after 12 hours treatment and the percentage of viable cells decreased after 48 hours treatment and the percentage of late apoptosis were increased. The compounds also induced DNA damage and caused DNA fragments that were visible on agarose gel for 24, 48, and 72 hours. The reactive oxygen species (ROS) production in treated cells can be detected using DCFI-I-DA. DAM caused high ROS production in WEHI-3B cells while NDAM caused high ROS production in HL-60 cells. The findings also suggest that these anthraquinones could be used as a cytotoxic agent against HL-60 and WEHI-3B cell lines primarily via apoptosis.